Rancang Bangun Aplikasi Stok Barang dengan QRcode Menggunakan Metode Waterfall dan Framwork Laravel pada Konveksi Sfgiandra - Pryatama, Daffa Nazza; Rukhviyanti, Novi (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
Konveksi SFgiandra is a company engaged in the purchase, sale, and inventory of hijab, with many customers relying on their services. However, the manual system applied in every sales transaction, calculation, and stock reporting often causes errors in calculations and slows down the process of making reports. This research aims to analyze and develop a stock application that can improve efficiency and accuracy in inventory management at SFgiandra Convection. The research method used is Waterfall, with design using the Laravel Framework and UML diagrams. Software testing is done with the Black Box concept. The results showed that the developed stock application allows checking goods more effectively and efficiently, helping Konveksi SFgiandra achieve its goals better